2022
DOI: 10.1016/j.esmoop.2022.100386
|View full text |Cite
|
Sign up to set email alerts
|

Expert opinion on management of pancreatic exocrine insufficiency in pancreatic cancer

Abstract: Pancreatic exocrine insufficiency (PEI) is a common condition in patients with pancreatic cancer (PC). PEI can be due to the tumor, which, if located in the head, causes obstruction of the pancreatic duct with subsequent atrophy of the pancreatic parenchyma, or it can be the consequence of pancreatic surgical resection. The standard treatment of PEI is pancreatic enzyme replacement therapy (PERT). Clinical data to support the use of PERT in PC are however limited. There are very few randomized clinical trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
0
12
0
5
Order By: Relevance
“…25 EPI is a contributing factor to malnutrition in both resectable and nonresectable PDAC owing to increased fecal fat and energy loss. [25][26][27][28] A small study assessed whether steatorrhea in PDAC could be related to enterocyte function rather than malabsorption using the citrulline generation test and ultimately concluded that EPI was responsible for fat malabsorption in this population. 26 Therefore, the mechanism of EPI in PDAC appears to be due to the tumor replacing functional acinar cells and/or obstructing the pancreatic duct, resulting in a deficiency of pancreatic enzymes at the duodenum.…”
Section: Exocrine Pancreatic Insufficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…25 EPI is a contributing factor to malnutrition in both resectable and nonresectable PDAC owing to increased fecal fat and energy loss. [25][26][27][28] A small study assessed whether steatorrhea in PDAC could be related to enterocyte function rather than malabsorption using the citrulline generation test and ultimately concluded that EPI was responsible for fat malabsorption in this population. 26 Therefore, the mechanism of EPI in PDAC appears to be due to the tumor replacing functional acinar cells and/or obstructing the pancreatic duct, resulting in a deficiency of pancreatic enzymes at the duodenum.…”
Section: Exocrine Pancreatic Insufficiencymentioning
confidence: 99%
“…Tumor histology, tumor location, and treatment modalities for PDAC impact prevalence rates. 28,29 For example, a meta-analysis by Iglesia et al identified a higher prevalence of EPI in tumors of the head than tumors of the tail of the pancreas (56% vs 32%, respectively). 25 Notably, among individuals who undergo pancreatic resection involving the pancreatic head, the risk of EPI is particularly increased because of the combination of altered gastrointestinal anatomy resulting in postcibal asynchrony, reduced enzyme stimulation due to neurohormonal changes, and/or reduction in functional pancreas volume.…”
Section: Exocrine Pancreatic Insufficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…It is also appropriate to administer PERT to achieve optimal nutritional status in all patients who have received neoadjuvant or adjuvant therapy or palliative therapy. The effectiveness of PERT is evaluated based on the alleviation of maldigestion-related symptoms (e.g., steatorrhea, weight loss, flatulence) and the normalization of the patients' nutritional status [57]. Proton pump inhibitors can be given as adjuvant therapy to prevent inactivation of PERT by gastric acids and thus improve the response [58].…”
Section: Exocrine Pancreatic Insufficiency and Malnutritionmentioning
confidence: 99%